2021
DOI: 10.3390/su131910985
|View full text |Cite
|
Sign up to set email alerts
|

Applying Importance–Satisfaction Model to Evaluate Customer Satisfaction: An Empirical Study of Foodpanda

Abstract: Because of improving mobile platforms and faster 4G speed, the annual growth of mobile devices has exceeded 50%, and many catering enterprises have integrated services to make ordering and delivery more convenient for smartphone users. Thus, user satisfaction with new online food-delivery platforms and services needs to be explored and evaluated. Using an Importance–Satisfaction Model (I–S Model), this study applied 12 service elements obtained from previous studies and an in-depth discussion of experts and sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…Sebastian and Findawati [9] research suggests that many customers may not be familiar with the store's location and desire a model to suggest a location based on data inputs. Additionally, Liu et al [10] found that Foodpanda prioritizes customer satisfaction by leveraging location and data, consistently achieving delivery times within 20 minutes. Harnessing data science and machine learning enables predicting the optimal route, considering customers' locations, and optimizing the selection of drivers and restaurants.…”
Section: Stream Analytics Geospatial Analyticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sebastian and Findawati [9] research suggests that many customers may not be familiar with the store's location and desire a model to suggest a location based on data inputs. Additionally, Liu et al [10] found that Foodpanda prioritizes customer satisfaction by leveraging location and data, consistently achieving delivery times within 20 minutes. Harnessing data science and machine learning enables predicting the optimal route, considering customers' locations, and optimizing the selection of drivers and restaurants.…”
Section: Stream Analytics Geospatial Analyticsmentioning
confidence: 99%
“…Liu et al [10] research reveals an increase in the demand for services, with many restaurants opting to utilize popular delivery platforms such as Grab and Foodpanda. However, customer satisfaction is contingent on the performance of third-party fleets.…”
Section: Business Issuesmentioning
confidence: 99%
“…The Importance-Satisfaction rating is based on the concept that public agencies will maximize overall customer satisfaction by emphasizing improvements in those areas where the level of satisfaction is relatively low and the perceived importance of the service is relatively high [35]. This method is easy to understand and has high popularity, so it is widely used as an important tool for evaluating and judging the satisfaction of the masses.…”
Section: I-s (Importance-satisfaction) Modelmentioning
confidence: 99%
“…Many studies have pointed out that the Performance Evaluation Matrix (PEM) is a convenient and useful tool for evaluating, analyzing, and improving service operating systems (Liu, Chen, & Zhang, 2021). This study adopts Chen's (2011) theory and revises the X-axis to represent "Importance" as a variable, while the Y-axis represents "Satisfaction."…”
Section: 096mentioning
confidence: 99%
“…The I-S model has been applied in various studies, including improvements in employee satisfaction in the spa industry (S.-H. Chen, 2012), member satisfaction surveys in Rotary clubs (B.-S. Chen & Chen, 2016), enhancement of management systems in higher education organizations (Tsai, Huang, & Yang, customerstomers satisfaction analysis in Foodpanda's delivery services (Liu et al, and 2021), improvement of job satisfaction among high-tech employeesthe using quality loss function theory (S. Chen,et alg t the the ), and enhancement of hotel lobby design through the integration of the Kano method (HTsai& Tsaih, 2022). These related studies have found that the I-S Model is a simple yet valuable tool for improving satisfaction, enhancing service quality, and managing product design (Liu et al, 2021;C. C. Yang, 2003).…”
Section: Lowmentioning
confidence: 99%